Peningkatan Kapasitas Pelaku Usaha Keripik Singkong Mentah di Kabupaten Solok melalui Pelatihan Manajemen Usaha dan Penguatan Nilai Spiritual - Yohan Fitriadi; Wellia Novita; Puspita Rama Nopiana (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program aims to improve the capacity of 25 raw cassava chip MSMEs in Solok Regency through holistic training that integrates managerial, collaborative, and spiritual aspects. The activities are designed with the real needs of business actors in mind, both in terms of technical business management skills and strengthening business ethics values. The training is conducted in a classical manner through the delivery of entrepreneurship and financial management materials covering basic business management concepts, simple marketing strategies, and cash flow management. In addition, participants participate in group simulations and ice-breaking games to foster a spirit of collaboration and build trust among business actors. Assistance in financial recording practices is carried out using the financial records application v1.1, which is designed to facilitate recording daily transactions, tracking production costs, and simple profit and loss analysis. A special contemplation session is also held to foster awareness of ethics and spirituality in entrepreneurship, including the importance of honesty, social responsibility, and sincere intentions in running a business. The program is evaluated through a 20-question digital quiz taken by all participants. The evaluation results show a significant increase in the understanding of basic management concepts, cash flow recording skills, and a responsible attitude in managing the business. These findings confirm that a values-based training approach combined with hands-on practice can effectively strengthen the foundations of MSME sustainability, both in terms of operational performance and moral resilience. Given the positive results, this program is recommended for replication in other regions with similar business characteristics. Continued support from local governments, educational institutions, and business partners is essential to expand the program's impact, ensure business sustainability, and foster competitive and integrated community-based economic growth.